What is blockchain? - Frossard Silva-Rêgo, Bernardo; Moura, Stephanie T.G (Henry Stewart Talks, 2023)
Smart contracts, Non-fungible tokens (NFTs), Blockchain benefits, Example of blockchain and smart contracts (Brilliant Earth), Example of blockchain and NFTs (Milton Nascimento)